Keanekaragaman Kupu-Kupu (Lepidoptera) di Sekitar Pinggiran Sungai Maslete Kabupaten Timor Tengah Utara - Nino, Maria Mathilda (BIO-EDU: Jurnal Pendidikan Biologi, 2019)
Research on butterfly diversity has been carried out, especially in Java, but not all regions in Indonesia have obtained data on butterfly diversity. One in the North Central Timor Regency is still not much done, especially around the banks of the river Maslete, North Central Timor Regency. The purpose of this study was to determine the types of butterflies, to know the diversity of butterflies, to determine environmental factors that affect the life of butterflies around the banks of the river Maslete, North Central Timor Regency and to determine the implementation of research results in learning biology in school. The method used in this study is the roaming method. Determination of sampling locations is done by purposive sampling method. Sampling was carried out by following a 500m transect line, the transect line was made on the transect line. The distance between subtransects is 250m. In each subtransect, 2 plots of 5x5 m2 were made. Butterflies are captured using nets and identification is based on the morphological characteristics of the butterfly. The data obtained were analyzed for diversity using the Shannon-wienner diversity index. The results of research around the banks of the river maslete found 7 types of butterflies belonging to 3 families namely Pieridae with 3 types, Nymphalidae with 2 types and Papilionidae with 2 types. The index of butterfly diversity around the banks of the Maslete River is relatively low with an H value of 0.9884. The results of measurements of environmental parameters around the Maslete riverbanks show that air temperatures range between 34.37-34.67o C and humidity ranges between 57-59%.